Does Movement Matter? Prefrontal Cortex Activity During 2D vs. 3D Performance of the Tower of Hanoi Puzzle - Milla, Kimberly; Bakhshipour, Elham; Bodt, Barry; Getchell, Nancy (Frontiers in Human Neuroscience, 2019)
In the current study, we used functional near infrared spectroscopy (fNIRS) to compare prefrontal cortex (PFC) activity in adults as they performed two conditions of the Tower of Hanoi (ToH) disk-transfer task that have equivalent executive function but different motor requirements. This study explored cognitive workload, here defined as the cognitive effort utilized while problem-solving by performance output. The first condition included a two-dimensional (2D) computerized ToH where participants completed trials using a computer mouse. In contrast, our second condition used a traditional, three-dimensional (3D) ToH that must be manually manipulated. Our aim was to better understand the role of the prefrontal cortex in these two conditions to detect if prefrontal cortex activity increases as a function of motor planning. Twenty right-handed, neurotypical adults (10M/10F, x̅ = 24.6, SD ± 2.8 y.o.) participated in two blocks (one per condition) of three one-minute trials where they were asked to solve as many puzzles as possible. These data were analyzed using a mixed effects ANOVA with participants nested within blocks for 2D vs 3D conditions, presentation order (leading block), individual participants, and regions and additional follow-up statistics. Results showed that changes in oxygenated hemoglobin, ΔHbO, were significantly higher for 3D compared to 2D condition (p=0.0211). Presentation order and condition interacted significantly (p=0.0015). Notably, a strong correlation between performance and ΔHbO existed between blocks 1 and 2 (r=-0.69, r2=0.473, p<0.01) when the 3D condition was initially performed, in contrast to the 2D condition where no significant correlation was seen. Findings also showed a significant decrease in ∆HbO between the first and second block (p=0.0015) while performance increased significantly for both 3D and 2D conditions (p<0.005). We plan to use this information in the future to narrow the potential points of impairment on the perception-cognition-action continuum in certain developmental disabilities.